The effects of pension rights and retirement age on training participation: evidence from a natural experiment - Raymond Montizaan; Frank Cörvers; Andries De Grip (Institute for the Study of Labor (IZA), 2009)
This paper uses a natural experiment approach to identify the effects of an exogenous change in future pension benefits on workers' training participation. We use unique matched survey and administrative data for male employees in the Dutch public sector who were born in 1949 or 1950. Only the latter were subject to a major pension reform that diminished their pension rights. We find that this exogenous shock to pension rights postpones expected retirement and increases participation in training courses among older employees, although exclusively for those employed in large organizations.
urn:nbn:de:101:1-200910141413
Keywords: J14; J24; J26; 330; Natural experiment; retirement; training; Ältere Arbeitskräfte; Rentenreform; Wirkungsanalyse; Altersgrenze; Bildungsverhalten; Weiterbildung; Niederlande